2020
DOI: 10.35810/ects.v1i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Coronary Artery Bypass Grafting Surgery after Acute Myocardial Infarction

Abstract: Background: Optimal timing for CABG surgery after myocardial infarction remains a matter of debate. The aim of our study was to analyze the effect of timing of CABG after acute myocardial infarction on operative mortality and morbidity. Methods: This prospective study included 60 patients who underwent isolated CABG within 30 days of acute myocardial infarction over 20 months (from the first of November 2014 till the end of June 2016) in Kasr Al-Ainy University Hospitals. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Off-pump beating heart coronary surgery is a preferred procedure for patients who need immediate coronary bypass surgery due to myocardial infarction. Several studies have demonstrated that off-pump beating heart surgery yields comparable cardiac outcomes to traditional CABG procedures [6][7][8][9]. Although off-pump beating heart surgery has been proven to be effective and safe when compared to conventional CABG (which is associated with side effects of CPB, problems from cross clamp usage, and cardioplegia), some opponents argue that achieving full revascularization may be challenging in the majority of off-pump patients.…”
Section: Discussionmentioning
confidence: 99%
“…Off-pump beating heart coronary surgery is a preferred procedure for patients who need immediate coronary bypass surgery due to myocardial infarction. Several studies have demonstrated that off-pump beating heart surgery yields comparable cardiac outcomes to traditional CABG procedures [6][7][8][9]. Although off-pump beating heart surgery has been proven to be effective and safe when compared to conventional CABG (which is associated with side effects of CPB, problems from cross clamp usage, and cardioplegia), some opponents argue that achieving full revascularization may be challenging in the majority of off-pump patients.…”
Section: Discussionmentioning
confidence: 99%
“…With advancements in myocardial protection tactics, anesthetics, and surgical procedures, CABG has become a generally safe and effective procedure. However, it is important to note that despite these improvements, there are still instances of significant mortality and morbidity rates reported in emergency traditional CABG following acute myocardial infarction (AMI) [2,12,13]. This high prevalence can be attributed to the patient's poor preoperative condition, which encompasses factors such as cardiogenic shock, organ failure, and myocardial injury resulting from cardioplegic arrest.…”
Section: Discussionmentioning
confidence: 99%